Increasing capacity of rural clients to access economic development programs: The Ontario BRE case study. Issue 2 (15th March 2017) - Oosterbaan, Catherine; Morris, Stephen
Abstract: Recognizing the importance of a meaningful business visitation program as a mechanism to monitor the health of a business community, the Ontario Ministry of Agriculture, Food, and Rural Affairs (OMAFRA) has supported rural municipalities and organizations in their implementation of business retention and expansion (BRE) programs since 1998. Since that time, OMAFRA has provided support for over 240 community/volunteer-led projects, with more than 9000 businesses surveyed across the province. As OMAFRA's clients and the economy continue to evolve, the program has benefitted from a number of updates. This article will examine how OMAFRA adapted its BRE program to enhance the capacity of its rural clientele to undertake the program and implement-related strategic economic development outcomes. These findings can inform other state and provincial-level programs to prepare their clientele to be successful with BRE.